Proudução de lipase por Candida rugosa e Geotrichum candidum empregando melaço de soja - Morais Júnior, Wilson Galvão de (2013)
Lipase (EC 3.1.1.3), an enzyme that hydrolyses the esters in glycerol, is often used for biotechnological and industrial applications. Candida rugosa and Geotrichum candidum lipases are known to have characteristics such as broad substrate specificity, tolerance toward organic solvents and high thermal stability. These characteristics permit the lipase to be used as a biocatalyst in industrial applications that are performed at elevated temperatures or in the presence of organic solvents. In this way, the present work describes the production of lipase by Candida rugosa and Geotrichum candidum in a culture supplemented with soybean molasses. After optimizing the fermentation times for both microorganisms, the effects of changing the soybean molasses concentration, the fermentative environment pH and the fermentation temperature were evaluated. When soybean molasses was used at a concentration of 200 g/L at 25 ºC, the lipolytic activity measured in the broth was 5.25 U/mL after 12 hours for Candida rugosa and 6.25 U/mL after 24 hours for Geotrichum candidum. Central composite planning (CCP) was used to define the optimal combination of soybean molasses concentration, initial environmental pH and fermentation temperature. This analysis determined that, in a medium containing 200 g/L soybean molasses at pH 3.5 ± 0.1 and a fermentation temperature of 27 ± 1 °C, the lipase activity increased by an average of 2.12 U/mL for Candida rugosa, representing an increase of 129% compared with the activity obtained in preliminary tests, and 11.48 U/mL for Geotrichum candidum, representing an increase of 84% compared with the activity obtained in preliminary tests. Furthermore, microbial lipases are usually purified with polymer/polymer and polymer/salt ATPSs (Aqueous two-phase systems). The findings of these purification experiments were promising, suggesting that the polymer/polymer and polymer/salt ATPSs could potentially be adopted for industrial-scale operation. ATPSs have achieved desired purification of lipases derived from microbial sources in less time than conventional multi-step downstream. The present work describes the purification of lipase derived from Candida rugosa and Geotrichum candidum, produced in a culture supplemented with soybean molasses. Alcohol/salt-based aqueous two-phase systems (ATPSs) were used to recover these lipases. Six biphasic systems, comprised of an alcohol-based top phase (ethanol and 2-propanol) and a salt-based bottom phase (potassium phosphate, sodium citrate and ammonium sulfate), were evaluated for their effectiveness in lipase recovering. The stability of lipase in each of the solutions was tested. From the results obtained in preliminary tests was held Central Composite Planning (CCP) in order to optimize the purification of lipases by ATPS. The optimum partition efficiency for purification of lipase for both micro-organisms was obtained in an ATPS of 20% (w/w) 2-propanol and 20% (w/w) potassium phosphate. The Candida rugosa lipase purified had a mean selectivity of 292.54, mean purification factor of 12.13 and a mean yield of 95.57%, while for Geotrichum candidum lipase purified had a mean selectivity of 272.78, mean purification factor 11.40 and a mean yield of 95.70%.